Voices from within experiences of patriarchy in traditional marriage and family life of high caste class Hindu women of Kathmandu - Karki, Anita Khadka
This study has looked into the narratives of lived experiences of the high caste/class if Hindu women of Kathmandu, who are both educated and working. With the help of the life stories narrated by ten women, including my own, the study sets out to show the Hindu traditional values function persistently, strongly at every stage of our lives, in spite of the fact that we neither suffer from poverty nor illiteracy. The study looked into various stages of the lives of the participants in the study, from childhood to adulthood...